2014
DOI: 10.1002/smr.1642
|View full text |Cite
|
Sign up to set email alerts
|

A mapping study on the feasibility of method engineering

Abstract: Software processes have become inherently complex to cope with the various situations we face in project environments. In response, the research area of method engineering arose in the 1990s aiming at the systematization of process construction and application. Although the research area has gained much attention and offered a plethora of contributions so far, we still have little knowledge about which basic concepts are finally established and what their feasibility is. To overcome this shortcoming, we need a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 73 publications
(126 reference statements)
0
24
0
1
Order By: Relevance
“…A similar conclusion was reached in 1997 by Ter Hofstede et al [13], who stated that more empirical research was needed to substantiate the claims associated with the potential benefits of ME. Despite these demands for more empirical research, two decades later it is still hard to find empirical studies that investigate methods and tools for ME [11].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar conclusion was reached in 1997 by Ter Hofstede et al [13], who stated that more empirical research was needed to substantiate the claims associated with the potential benefits of ME. Despite these demands for more empirical research, two decades later it is still hard to find empirical studies that investigate methods and tools for ME [11].…”
Section: Related Workmentioning
confidence: 99%
“…Kuhrmann et al concluded in a recent mapping study [11] that there are hardly any reports on the practical application of ME available in the literature. Henderson-Sellers et al argue in [2,12] that practitioners often fail to see the usefulness of ME mainly due to its complexity and cost in terms of time, money, and people.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, we used MOSKitt as the base platform for implementing the CAME environment that is presented in this thesis: MOSKitt4ME. [3] and later by Kuhrmann et al in [11].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Kuhrmann et al concluded in a recent mapping study [11] that there are hardly any reports on the practical application of Method Engineering available in the literature. Henderson-Sellers et al argue in [3,31] that practitioners often fail to see the usefulness of Method Engineering mainly due to its complexity and cost in terms of time, money, and people.…”
Section: Research Motivationmentioning
confidence: 99%
See 1 more Smart Citation